FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR CPO PROVINSI LAMPUNG - Adi Muhammad Muslih; Wan Abbas Zakaria; Eka Kasymir (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2013)
This research objective was to analyze the factors that affect the CPO exports of Lampung Province. The research was conducted in Lampung Province and used secondary data. The data was collected in July 2012 from several departments and agencies related to this research. The factors that affect the CPO export in Lampung Province were analyzed by using Ordinary Least Square (OLS) method. The results of this study indicated that the CPO export of Lampung Province was positively affected by the CPO production, the international price of CPO, and palm oil prices. In addition, it was negatively affected by the domestic CPO prices and CPO export tax of Lampung Province.   Keywords: Crude Palm Oil (CPO), export, Lampung Province